An Efficient Method Using Modified Transmission Gate for Bio Medical Applications (International Journal of Scientific Research in Science and Technology, 2025)
A novel method is presented here, using modified transmission gate exclusively for IOT application in biomedical area. The major advantage is there is no peripheral circuitry requirement during a read operation. For the purpose of efficient power consumption SRAMs are used in our project. We focus on biomedical area as it typically operates in the sub-threshold domain with good efficiency. In order to reduce the power consumption for the circuit we are applying the power gating technique at the supply node. The proposed design is used for low power technology as well as a technology for low power consumption. Thus, by using the power gating technique we are making the 8T SRAM as power efficient and effective read operation stability.